Rekonstruksi Peran Judex facti dalam Perkara Narkotika: (Analisis Putusan Banding Nomor 130/PID.SUS/2023/PT DKI) - Setiawan, Junet Hariyo (Fakultas Hukum Universitas Andalas, 2025)
This study examines the function of judex facti exercised by the High Court in narcotics criminal cases, with a particular focus on the appellate decision Number 130/PID.SUS/2023/PT DKI involving a high-ranking law enforcement officer. Within the Indonesian legal system, the High Court is mandated to perform a substantive corrective role by re-evaluating facts and evidentiary materials, including digital evidence, to ensure both procedural and substantive justice. Employing a normative juridical approach, this research analyzes statutory regulations, legal doctrines, and relevant judicial decisions. The findings reveal that the High Court failed to exercise its corrective function effectively: no forensic verification was conducted on digital evidence, the defendant's confession was accepted without independent corroboration, and the standards for digital evidence as stipulated in Supreme Court Regulation No. 4 of 2020 were disregarded. As a result, the appellate ruling merely confirmed the first-instance judgment without substantive reconsideration. This study recommends an amendment to the Indonesian Code of Criminal Procedure (KUHAP) to explicitly regulate digital evidence, alongside the development of technical guidelines and capacity building for judges in assessing electronic evidence. Such reforms are essential to reinforce judicial accountability and safeguard impartial justice in narcotics cases involving institutional actors.